The influence of blogs on the complain intention: the case of the cruise ship industry - Gonzales Santiago, Marcya (2019)
This paper investigates the influence of service recovery in the consumer's complaint intention to obtain benefits on the cruise industry. The research model proposed and tested empirically was based on a sample of 164 cruise vacationers who had experiences of a past service failure. The model also shows the influence of cruise blogs on consumer’s complaint intention. The result of the analysis demonstrates higher influence of cruise blogs and reviews than service recovery strategies on the complaint intention. The findings of the study provide a better understanding of the service recovery on the cruise industry, being useful for the managers of the cruise companies. Finally, the results suggest, as well, that cruise ship managers should implement new marketing strategies related to service recovery and at the same time attract cruise blogs to the company.